Strategi Komunikasi Pemasaran Digital Film Agak Laen: Menyala Pantiku! Melalui Konten Instagram - Permatasari, Oktavia (Da’watuna: Journal of Communication and Islamic Broadcasting, 2026)
In the digital era, film marketing communication strategies have shifted from traditional methods such as advertisements and physical posters to more adaptive digital strategies in keeping up with technological developments. One of the digital media used in marketing for film promotion is social media. Social media is one of the platforms capable of reaching a wider audience quickly, thus surpassing previously used conventional methods. This requires the film industry to be adaptive and innovative in understanding digital consumer behavior. One of the social media that is an effective means of conducting digital marketing communication is Instagram. The film Agak Laen: Menyala Pantiku! is one of the films that implements a digital marketing communication strategy through Instagram. It has proven successful by reaching more than 10 million viewers and becoming the highest-grossing film of all time in Indonesia. This study aims to analyze the digital marketing communication strategy of the film Agak Laen: Menyala Pantiku! through Instagram content using the AISAS model (Attention, Interest, Search, Action and Share). The research method was carried out through observation and literature studies with a descriptive qualitative approach. The results of the study show that based on the analysis of the AISAS model, it is one of the efforts to attract public attention. Especially in the share indicator, where people recommend watching it. This research is useful as a reference in designing digital marketing communication strategies on social media by understanding the target audience, consumer behavior patterns and the application of the AISAS model.